Technology Integration in Problem-Based Culturally Responsive Mathematics Learning: A Systematic Literature Review in the Era of Industry 5.0 - Fitri, Rahmia Mulya; Al Jupri; Mulyaning, Endang Cahya; Sitanggang, Damra Ali (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
The Industry 5.0 era demands mathematics learning models that are not only technology-enhanced but also culturally responsive and competence-oriented. This systematic literature review investigates the integration of technology-supported problem-based learning (PBL) with culturally responsive teaching (CRT) in mathematics education. Following the PRISMA 2020 protocol, 24 records were retrieved from Scopus, ScienceDirect, and Google Scholar; five met the inclusion criteria and were thematically analyzed. Results show that PBL supported by technology improves students’ problem-solving skills, mathematical literacy, motivation, and self-regulated learning. However, explicit integration of CRT within these models remains limited. Compared to conventional approaches, a combined PBL-CRT-technology framework holds greater potential to promote meaningful, inclusive, and future-oriented mathematics learning. This review recommends the development of a comprehensive instructional model that aligns cultural relevance, digital innovation, and inquiry-based learning. Implications for research and practice are outlined to support mathematics education in diverse and digitally connected learning environments.